Building an Aggregate Index to Measure the Stress of the Financial System in Syria during the Period 2010-2021 (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aimed to build an aggregate index to measure the stress of the financial system in Syria, by using a set of sub-indicators to measure the stress in four main financial markets of the Syrian financial system (the banking market, the stock market, the foreign exchange market, and the external debt securities market).Financial stress in the financial system markets was measured using the ratio of non-performing loans, the ratio of loans to deposits, The growth rate of market index returns multiplied by minus one, the realized volatility of the stock market, the maximum accumulated loss of the exchange market, the realized volatility of the exchange market, the growth rate of external debt, The ratio of external debt to GDP, and the ratio of external debt to exports. The sub-indices were then grouped into one indicator using the equal weights method.The study used quarterly data for financial stress indicators during the period extending from the first quarter of 2010 until the third quarter of 2021.The study concluded with constructing an aggregate index capable of measuring the stress of the Syrian financial system and identifying periods of financial stress well.